The design of a high aspect ratio HALE aircraft composite wing. part I: static strength analysis / Bambang K. Hadi, Muhammad A. Ghofur and IndraPermana - Hadi, Bambang K.; Ghofur, Muhammad A.; Permana, Indra (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2015)
High Altitude Long Endurance (HALE) UAV is a type of aircraft that is able to fly in high operational altitude (±65,000 ft) and longer duration (±36 hours). This aircraft uses a high aspect ratio wing, up to 25. In this paper, the design of a high aspect ratio wing will be performed. The Global Hawk RQ-4A was used as a test case. Static strength analysis with Tsai-Wu failure criteria will be used. The carbon/epoxy T300/5208 is selected and the results will be compared with the use of aluminum 2024-T3. Two laminate configurations were used in this study. They were (0°/0°/+450°/-45°)s and a quasi-isotropic (0°/+45°/-45°/90°)s. The aim of the study was to find a minimum weight while fulfilling the strength criteria. Finite Element Method was used extensively during the study, using NASTRAN software. The results showed that the wing with laminate configuration of (0°/0°/+450°/-45°)s was 30% lighter than the one with quasi-isotropic configuration, and was 60% lighter than the aluminum wing.